Pengembangan Model Pembelajaran Biola Bagi Siswa Tahap Pemula Untuk Pembentukan Ketrampilan dan Karakter Cinta Tanah Air - Irwan Bakhti; Robinson Situmorang; Khaerudin - (Peneliti.net, 2018)
The purpose of this research is to develop a learning system that is close to the learning environment itself, using Indonesian cultural content that is National songs, children, Indonesian area. This research was conducted at two music course institutions in Jakarta involving three violin teachers. Stages of observation were carried out in August 2016 at the Institute for Educational Music in Farabi and Willy Sumantri Music School. The method used in this study is Reasech and Devolution (research and development). Research and development to make or develop a product, both in the commercial and educational sectors. The model used in this research is the MPI model. The results of the validation by the experts showed that the average test of the material expert was 3.77, the media expert obtained 3.0, the design expert obtained a score of 3.0, which meant that the product was feasible and very good to use. Furthermore the product will be tested to a number of students with small group stage ie 3 respondents with face to face method obtained the overall average value of 73.33, small group trial obtained overall average value 90. Conclusion learning module violin for novice stage students to the formation of skills and the character of love for the homeland can be said to be good or worthy of use.